Molecular imprinted polymer shell on goethite nanorod core for creatinine identification and measurement - Amininasab, Seyed Mojtaba; Holakooei, Parvin; Shami, Zahed; Jaliliyan, Elham (Journal of Composites and Compounds, 2022)
A new creatinine molecular imprinted polymer on the surface of goethite nanorods (CMIPG) was synthesized using the core-shell structure for the absorption and identification of creatinine. Nano goethite particles (NG) that had been modified with fumaric acid were employed as a core, and a polymerization procedure was carried out in the methacrylic acid (MAA) presence as a functional monomer and creatinine as a template on the surface of the modified goethite nanorods (MGN). Characterization of the CMIPG by energy dispersive spectroscopy-coupled scanning electron microscopy (SEM-EDS), field emission scanning electron microscopy (FESEM), Fourier transform infrared (FT-IR), and thermal gravimetric analysis (TGA) showed that the polymerization was successful. The effect of different factors such as pH, contact time, the amount of the adsorbent, imprinting efficiency, and primary creatinine concentration on creatinine adsorption capacity of CMIPG were evaluated and the results showed that recognition sites were created on the nanoparticles’ surface through the polymerization process. The ability of CMIPG for selective identification was studied by the binary solution of creatinine and its analogous such as creatine, L-tyrosine, and N-hydroxysuccinimide (NHS) revealing its ability to selectively absorb creatinine. Moreover, the CMIPG's release and reusability, isotherm, and kinetic models were examined.